2002
DOI: 10.1364/ol.27.001752
|View full text |Cite
|
Sign up to set email alerts
|

Observation of an x-ray vortex

Abstract: Phase singularities are a ubiquitous feature of waves of all forms and represent a fundamental aspect of wave topology. An optical vortex phase singularity occurs when there is a spiral phase ramp about a point phase singularity. We report an experimental observation of an optical vortex in a field consisting of 9-keV x-ray photons. The vortex is created with an x-ray optical structure that imparts a spiral phase distribution to the incident wave field and is observed by use of diffraction about a wire to crea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
79
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(81 citation statements)
references
References 13 publications
2
79
0
Order By: Relevance
“…Traditionally, these "optical vortices" are created by shaping of the phase front of a laser as it passes through different optical media [11][12][13], such as spiral phase plates [14] or computer generated holograms [15]. Analogous techniques have also been used to transform x-rays into vortices at synchrotron light sources [16,17], and alternate methods suggest vortex beams can be created through Compton back-scattering [18] or harmonic emission in undulators [19]. Here, we report on a completely different technique in which a simple Gaussian laser pulse is used to generate fully coherent l = 1 OAM light purely through its interaction with a relativistic electron beam (e-beam).…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, these "optical vortices" are created by shaping of the phase front of a laser as it passes through different optical media [11][12][13], such as spiral phase plates [14] or computer generated holograms [15]. Analogous techniques have also been used to transform x-rays into vortices at synchrotron light sources [16,17], and alternate methods suggest vortex beams can be created through Compton back-scattering [18] or harmonic emission in undulators [19]. Here, we report on a completely different technique in which a simple Gaussian laser pulse is used to generate fully coherent l = 1 OAM light purely through its interaction with a relativistic electron beam (e-beam).…”
Section: Introductionmentioning
confidence: 99%
“…This technique has been used in the past to produce XUV or x-ray beams that carry OAM [33,34]. However, for high-brightness short-wavelength FEL radiation, the damage threshold of optical elements placed into the beam path, and the difficulties in the fabrication of high quality optical surfaces, impose strong limitations on the use of this method.…”
mentioning
confidence: 99%
“…In addition to the theoretical results presented in this study, several groups have confirmed production of the xray vortex beams carrying well-defined angular momentum and radial variation in direct comparison to similar beams in other spectral regions. [43][44][45] Also, several groups of researchers around the world have proposed and tested methods for focusing x-rays from modern sources to beam sizes tens to hundreds of nm's across. [46][47][48] While many of these techniques focus on hard x-rays whose energy exceeds that of core electronic transitions, there is no a priori reason why similar techniques cannot be applied in the region of 200-1000 eV.…”
Section: Spontaneous Inelastic Scattering Of Lg Beams From Vibromentioning
confidence: 99%